A NEW SPECIES OF ZEUGOPHORA KUNZ~ FROM JAVA (COLEOPTERA: CHRYSOMELIDAE: MEGALOPODINAE) - C. A. M. Reid (Treubia, 1992)
Zeugophora javana sp, n. is described from West Java and placed in the subgenus Pedrillia. Diagnostic characters are given to separate Z. javana from other species in Australia.